Lives and Moments: An Introduction to Short Fiction - Ostrom, Hans. (Orlando Holt, Rinehart and Winston, Inc, 1991)
Lives and Moments is aimed at a college-level audience that is writing fiction, embarking on the study of literature, or familiarizing itself with the short story as a distinct genre. The anthology is also appropriate for introductory and intermediate courses in composition that include the study of short stories.
Keywords: Writing